Effects of Selenium Conjugated to Insect Protein on Pharmacokinetics of Florfenicol and Enrofloxacin in Laying Hens - Qiu, Kai; Obianwuna, Uchechukwu Edna; Wang, Jing; Zhang, Hai-jun; Qi, Guang-hai; Wu, Shu-geng (Frontiers in Veterinary Science, 2021)
In the context of increasing awareness on the dietary supplementation of organic selenium in commercial poultry production and ensuring egg safety, the present study investigated selenium effects on the pharmacokinetics of therapeutic use of florfenicol and enrofloxacin from perspectives of laying performance, selenium deposition in eggs, drugs residue in plasma, organs and eggs. A 2 × 3 factorial arrangement with two kinds of drugs (florfenicol vs. enrofloxacin, 200 mg/kg) and three levels of dietary organic selenium SCIP (selenium conjugated to insect protein) (0, 2, and 5 mg/kg) was designed together with a blank control group. Healthy Hy-Line Brown laying hens (n = 252, 40-week old and 90.0 ± 1.7% of egg production rate) were randomly allocated into 1 of 7 treatments with 6 replicates and 6 hens per replicate. The experiment lasted for 42 days and consisted of 3 periods (adjusted stage, depositional stage, and eliminating stage) of 14 days each. These stages entails: feeding of the laying hens with basal diets, addition of drugs and selenium synchronously into the diets, drug withdrawal from diet and supply of selenium uninterruptedly in the diet respectively. Egg production and feed intake were recorded on daily and weekly basis respectively. The selenium content in egg yolk, egg white and whole eggs, and the drug residues in eggs, plasma, liver, kidney and breast muscle were determined on day 2, 3, 5, 6, 7, 9, 11, and 14 of depositional and eliminating stages. There were no significant difference (P > 0.05) in egg production among the dietary treatments but feed intake decreased significantly (P < 0.05) in the drug treatment group compared to other groups. Dietary organic selenium decreased the residue of drugs in tissues and eggs, while metabolism and deposition of selenium in laying hens were suppressed due to drug effect. The results of the present study are of significance to enrich the knowledge of the pharmacokinetics of florfenicol and enrofloxacin in laying hens and ensure the safety of poultry products.